“EFECTO DEL DESARROLLO FINANCIERO, LA INVERSIÓN EXTRANJERA DIRECTA Y LAS EMISIONES DE CO2 A NIVEL GLOBAL Y POR GRUPOS DE INGRESOS UTILIZANDO DATOS DE PANEL, MEDIANTE TÉCNICAS DE COINTEGRACIÓN Y CAUSALIDAD, EN EL PERIODO 1970-2016” - Armijos Coronel, Yesenia Lizbeth (2019)
The objective of this study is to determine the effect of financial development and direct foreign investment on CO2 emissions globally and by income groups in the period 1970-2016. Panel data were used through cointegration and causality techniques. First, the cointegration test of Pedroni (1999) and Westerlund (2007) was used to find the long-term and short-term equilibrium. Also, the force of the cointegration vector was individually for countries through a Dynamic Ordinary Least Squares model (DOLS) and for groups of countries with a Dynamic Panel model with Ordinary Least Squares (PDOLS). In addition, through the tests of Dumitrescu and Hurlin (2012), the direction of causality between the series analyzed was verified. The results found, indicate the existence of short and long term equilibrium between the three variables worldwide and by groups of countries. Likewise, it was found that the strength of the cointegration vector is significant in several countries, but it does not present a convincing value. Finally, the results of the causality test show the existence of a unidirectional and bidirectional causal relationship between the variables. According to the obtained, policies aimed at the reduction of CO2 emissions are proposed, for this, it is important that the countries under investigation examine the regulation of foreign investment to promote environmental protection and increase the transfer of technology friendly with the environment. In addition, special loans with lower discounts should be considered. Once investments are aimed at products with low carbon content. In this way, both companies and individuals will demand products for the conservation of the environment.